Hydroxamic Acids Derivatives: Greener Synthesis, Antiureolytic Properties and Potential Medicinal Chemistry Applications - A Concise Review - Viana, Luciana P S; Pinheiro, Luan R; Petrillo, Lorenzo W; Medeiros, Isabela G; Rizo, Taina G; Modolo, Luzia V; da Silva, Cleiton M; de Fatima, Ângelo (Current topics in medicinal chemistry, 2025)
Hydroxamic acids (HAs) are chemical compounds characterized by the general structure RCONR'OH, where R and R' can denote hydrogen, aryl, or alkyl groups. Recognized for their exceptional chelating capabilities, HAs can form mono or bidentate complexes through oxygen and nitrogen atoms, rendering them remarkably versatile. These distinctive structural attributes have paved the way for a broad spectrum of medicinal applications for HAs, among which their pivotal role as inhibitors of essential Ni(II) and Zn(II)-containing metalloenzymes. In 1962, a significant breakthrough occurred when Kobashi and colleagues identified hydroxamic acids (HAs) as potent urease inhibitors. Subsequent research has increasingly underscored their capability in combatting infections induced by ureolytic microorganisms, including and . However, comprehensive reviews exploring their potential applications in treating infections caused by ureolytic microorganisms remain scarce in the scientific literature. Thus, this minireview aims to bridge this gap by offering a systematic exploration of the subject. Furthermore, it seeks to explore the significant advancements in obtaining hydroxamic acid derivatives through environmentally sustainable methodologies.